2002
DOI: 10.7182/prtr.12.3.f1125h237x090756
|View full text |Cite
|
Sign up to set email alerts
|

Transplant coordination as the "keystone" in non-heart-beating donations

Abstract: The shortage of donated organs has become a problem in the transplantation world. Transplant teams are continuously looking for new ways to increase and improve the donor pool. Non--heart-beating donors could be a source for increasing the number of donors, even though in some countries legal, ethical, or logistical problems obstruct the development of that source. The good results obtained by some groups working with non--heart-beating donors should stimulate others to implement this type of policy in their h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…transplant personnel and OPO staff conducted these sessions. Our experience in implementing these protocols was similar to that described by the Lifequest OPO in Florida (13), but quite different from non-U.S. experiences (14), as we found that the process requires a physician-champion and was essentially physician driven.…”
Section: Discussionsupporting
confidence: 49%
“…transplant personnel and OPO staff conducted these sessions. Our experience in implementing these protocols was similar to that described by the Lifequest OPO in Florida (13), but quite different from non-U.S. experiences (14), as we found that the process requires a physician-champion and was essentially physician driven.…”
Section: Discussionsupporting
confidence: 49%